A 10-year Trend of Sleeping Patterns, Geographical, and Community Disparities Among Chinese Older Adults. (May 2022) - Lee, Yi-Ting Hana; Lee, Yen-Han; Wu, Yu-Hsuan; Liu, Ching-Ti; Chang, Yen-Chang
This study examined the trend and geographical/community disparities of sleeping patterns among Chinese older adults. We included older adults from four waves of the Chinese Longitudinal Healthy Longevity Survey (CLHLS; n = 25, 672; age ≥65). We used a multivariable logistic regression model to examine sleep quality (not good versus good), and a multinomial logistic regression model to assess daily sleep duration (7–8 hr, <7 hr, >8 hr). Older adults from the Central/South and the West regions were less likely to report good sleep quality (AOR [adjusted odds ratio] = .63, 95% CI: .55, .72 and AOR = .80, 95% CI: .70, .93, respectively) while the Northeastern residents reported better sleep quality (AOR = 1.51, 95% CI: 1.27, 1.79), compared with Northern residents. Older adults from Central/South and West were more likely to obtain less than 7 hr of sleep. Public health interventions are necessary to improve the sleep of Chinese older adults.